Value of risk scores in the decision to palliate patients with ruptured abdominal aortic aneurysm. Issue 9 (6th April 2018) - Sweeting, M. J.; Ulug, P.; Roy, J.; Hultgren, R.; Indrakusuma, R.; Balm, R.; Thompson, M. M.; Hinchliffe, R. J.; Thompson, S. G.; Powell, J. T.
Abstract : Background: The aim of this study was to develop a 48‐h mortality risk score, which included morphology data, for patients with ruptured abdominal aortic aneurysm presenting to an emergency department, and to assess its predictive accuracy and clinical effectiveness in triaging patients to immediate aneurysm repair, transfer or palliative care. Methods: Data from patients in the IMPROVE (Immediate Management of the Patient With Ruptured Aneurysm: Open Versus Endovascular Repair) randomized trial were used to develop the risk score. Variables considered included age, sex, haemodynamic markers and aortic morphology. Backwards selection was used to identify relevant predictors. Predictive performance was assessed using calibration plots and the C‐statistic. Validation of the newly developed and other previously published scores was conducted in four external populations. The net benefit of treating patients based on a risk threshold compared with treating none was quantified. Results: Data from 536 patients in the IMPROVE trial were included. The final variables retained were age, sex, haemoglobin level, serum creatinine level, systolic BP, aortic neck length and angle, and acute myocardial ischaemia. The discrimination of the score for 48‐h mortality in the IMPROVE data was reasonable (C‐statistic 0·710, 95 per cent c.i. 0·659 to 0·760), but varied in external populations (from 0·652 to 0·761). The new score outperformed other published risk scores in some, but not all, populations. An 8 (95 per cent c.i. 5 to 11) per cent improvement in the C‐statistic was estimated compared with using age alone. Conclusion: The assessed risk scores did not have sufficient accuracy to enable potentially life‐saving decisions to be made regarding intervention. Focus should therefore shift to offering repair to more patients and reducing non‐intervention rates, while respecting the wishes of the patient and family. Abstract : Not much help